2019
DOI: 10.1155/2019/5741642
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Blending Degree between Virgin and Aged Binder on Pavement Performance of Recycled Asphalt Mixture with High RAP Content

Abstract: In this study, the influence of the blending degree between virgin and aged binder on the pavement performance of hot-mix recycled asphalt mixture (HMRAM) with high RAP content is analyzed. The aggregate gradation of AC-16 was selected. The RAP contents were 30, 40, and 50%. HMRAMs with different degrees of blending (DOBs) were prepared by changing the mixing temperature (150, 165, and 180°C) without the occurrence of excessive aging for asphalt binders. An improved Hirsch dynamic modulus prediction model was … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(3 citation statements)
references
References 15 publications
0
3
0
Order By: Relevance
“…Noferini et al [14] revealed that increasing the RAP percentage in the asphalt mixes caused more interactions between RAP binder and VAB, which increased the stiffnesses of the EABs. The 100% blending, full blending, between RAP binder and VAB did not reach, even so, the researchers [15] tried different RAP percentages and mixing temperatures. Thus, the full blending is a theoretical assumption that was not achieved.…”
Section: Introductionmentioning
confidence: 99%
“…Noferini et al [14] revealed that increasing the RAP percentage in the asphalt mixes caused more interactions between RAP binder and VAB, which increased the stiffnesses of the EABs. The 100% blending, full blending, between RAP binder and VAB did not reach, even so, the researchers [15] tried different RAP percentages and mixing temperatures. Thus, the full blending is a theoretical assumption that was not achieved.…”
Section: Introductionmentioning
confidence: 99%
“…These aspects are analyzed individually in other scientific papers, while this study presents a comprehensive analysis of all above-mentioned aspects, which is a particularity of the applied methodology. RAP material performances are highlighted in previous researches/studies for both types of origin source, namely unique source or single project site [1][2][3][4][5], as well as multiple sources or project sites [6][7][8][9][10][11][12] collected using milling or other techniques or produced in laboratory after applying long-term aging techniques [13]. Thus, RAP obtained from unique or multiple sources presents significant inhomogeneity and is prepared with pre-processing techniques such as screening, sieving, crushing, storing separately according to its gradation stockpiles [14,15], or even mixing and storing in hybrid RAP stockpiles [16] suitable for further use in a new asphalt mixture.…”
Section: Introductionmentioning
confidence: 99%
“…e surface aging degree of RAP is usually different from that of the RAP internal [5][6][7]. It was found that there was a big difference between the recycled asphalt and the asphalt because the mineral powder can absorb certain components in the asphalt [8].…”
Section: Introductionmentioning
confidence: 99%